PENGARUH DAYA TARIK IKLAN DAN ELECTRONIC WORD OF MOUTH (EWOM) TERHADAP MINAT PENGGUNA JASA TRANSPORTASI ONLINE GOJEK DI UNIVERSITAS BHYANGKARA KOTA BEKASI (Studi Kasus Mahasiswa S1 Manajemen Di Universitas Bhayangkara Kota Bekasi) - Franco Nero Rupelu; Supriyanto, Dody Kurniawan (ADISAM PUBLISHER, 2024)
The purpose of this study was to analyze the influence of Advertising Attraction and Electronic Word of Mouth (EWOM) on User Interest of Gojek online transportation services among students of Bhayangkara University, Bekasi City. The research method used is a quantitative method using a questionnaire distributed to 130 respondents. Data analysis was carried out using the t-test and f-test to test the hypothesis. The results of the study indicate that Advertising Attraction and Electronic Word of Mouth have a positive and significant influence on User Interest.